Global effect of the COVID-19 pandemic on paediatric cancer care: a cross-sectional study. (May 2021) - Graetz, Dylan; Agulnik, Asya; Ranadive, Radhikesh; Vedaraju, Yuvanesh; Chen, Yichen; Chantada, Guillermo; Metzger, Monika L; Mukkada, Sheena; Force, Lisa M; Friedrich, Paola; Lam, Catherine; Sniderman, Elizabeth; et al.
Summary: Background: Although mortality due to COVID-19 has been reportedly low among children with cancer, changes in health-care services due to the pandemic have affected cancer care delivery. This study aimed to assess the effect of the COVID-19 pandemic on childhood cancer care worldwide. Methods: A cross-sectional survey was distributed to paediatric oncology providers worldwide from June 22 to Aug 21, 2020, through the St Jude Global Alliance and International Society for Paediatric Oncology listservs and regional networks. The survey included 60 questions to assess institution characteristics, the number of patients diagnosed with COVID-19, disruptions to cancer care (eg, service closures and treatment abandonment), adaptations to care, and resources (including availability of clinical staff and personal protective equipment). Surveys were included for analysis if respondents answered at least two thirds of the items, and the responses were analysed at the institutional level. Findings: Responses from 311 health-care professionals at 213 institutions in 79 countries from all WHO regions were included in the analysis. 187 (88%) of 213 centres had the capacity to test for SARS-CoV-2 and a median of two (range 0–350) infections per institutution were reported in children with cancer. 15 (7%) centres reported complete closure of paediatric haematology-oncology services (median 10 days, range 1–75 days). Overall, 2% (5 of 213) of centres were no longer evaluating new cases of suspected cancer, while 43% (90 of 208) of the remaining centers described a decrease in newly diagnosed paediatric cancer cases. 73 (34%) centres reported increased treatment abandonment (ie, failure to initiate cancer therapy or a delay in care of 4 weeks or longer). Changes to cancer care delivery included: reduced surgical care (153 [72%]), blood product shortages (127 [60%]), chemotherapy modifications (121 [57%]), and interruptions to radiotherapy (43 [28%] of 155 institutions that provided radiotherapy before the pandemic). The decreased number of new cancer diagnoses did not vary based on country income status (p=0·14). However, unavailability of chemotherapy agents (p=0·022), treatment abandonment (p<0·0001), and interruptions in radiotherapy (p<0·0001) were more frequent in low-income and middle-income countries than in high-income countries. These findings did not vary based on institutional or national numbers of COVID-19 cases. Hospitals reported using new or adapted checklists (146 [69%] of 213), processes for communication with patients and families (134 [63%]), and guidelines for essential services (119 [56%]) as a result of the pandemic. Interpretation: The COVID-19 pandemic has considerably affected paediatric oncology services worldwide, posing substantial disruptions to cancer diagnosis and management, particularly in low-income and middle-income countries. This study emphasises the urgency of an equitably distributed robust global response to support paediatric oncology care during this pandemic and future public health emergencies. Funding: American Lebanese Syrian Associated Charities. Translation: For the Spanish translation of the abstract see Supplementary Materials section.